2017
DOI: 10.1002/ijgo.12264
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of conception subsequent to methotrexate treatment for an unruptured ectopic pregnancy

Abstract: The frequency of fetal malformation in a subsequent pregnancy was low among women treated with methotrexate for ectopic pregnancy. The frequency of early missed abortion was lowest during the first 6 months after treatment with methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…MTX has been used as a medical alternative to surgery for women with ectopic pregnancy since the 1990s (47). Previous studies demonstrated that MTX had a success rate of approximately 94% when administered to the appropriate patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…MTX has been used as a medical alternative to surgery for women with ectopic pregnancy since the 1990s (47). Previous studies demonstrated that MTX had a success rate of approximately 94% when administered to the appropriate patients (48).…”
Section: Discussionmentioning
confidence: 99%